Nonlinear pattern and algal dual-impact in N2O emission with increasing trophic levels in shallow lakes. (15th September 2021) - Zhou, Yiwen; Xu, Xiaoguang; Song, Kang; Yeerken, Senbati; Deng, Min; Li, Lu; Riya, Shohei; Wang, Qilin; Terada, Akihiko
Highlights: Net N2 O emissions from shallow lakes depend on eutrophication progress. N2 O emissions of different lakes were distinguished by a nonlinear model. Algal accumulation plays a dual role in regulating N2 O emissions. N2 O emission fluxes were higher in winter than in summer in shallow lakes. N2 O emissions in eutrophic lakes were overestimated by IPCC. Abstract: Shallow lakes are considered important contributors to emissions of nitrous oxide (N2 O), a powerful greenhouse gas, in aquatic ecosystems. There is a large degree of uncertainty regarding the relationship between N2 O emissions and the progress of lake eutrophication, and the mechanisms underlying N2 O emissions are poorly understood. Here, N2 O emission fluxes and environmental variables in different lakes along a trophic state gradient in the Yangtze River basin were studied. N2 O emission fluxes were –1.0–53.0 μg m –2 h –1 and 0.4–102.9 μg m –2 h –1 in summer and winter, respectively, indicating that there was marked variation in N2 O emissions among lakes of different trophic state. The non-linear exponential model explained differences in N2 O emission fluxes by the degree of eutrophication ( p < 0.01). TN and chl-a both predicted 86% of the N2 O emission fluxes in shallow lakes. The predicted N2 O emission fluxes based on the IPCC EF5r overestimated the observed fluxes, particularly those in hyper-eutrophic lakes. These findings demonstrated that nutrient-rich conditions and algal accumulation are key factors determining N2 O emission fluxes in shallow lakes. Furthermore, this study also revealed that temperature and algae accumulation-decomposition determine an N2 O emission flux in an intricate manner. A low temperature, i.e., winter, limits algae growth and low oxygen consumption for algae decomposition. The environment leaves a high dissolved oxygen concentration, slowing down N2 O consumption as the final step of denitrification. In summer, with the oxygen consumed by excess algal decomposition, the N2 O production is limited by the complete denitrification as well as the limited substrate supply of nitrate by nitrification in hypoxic or anoxic conditions. Such cascading events explained the higher N2 O emission fluxes from shallow lakes in winter compared with summer. This trend was amplified in hyper-eutrophic shallow lakes after algal disappearance. Collectively, algal accumulation played a dual role in stimulating and impeding N2 O emissions, especially in hyper-eutrophic lakes. This study expands our knowledge of N2 O emissions from shallow lakes in which eutrophication is underway. Graphical abstract: Image, graphical abstract